A comparative study of the geomagnetic S and L fields in the low latitude region - RAO, K.S. RAJA (MAUSAM, 1962)
In separate communications (1962 a, b) the author has discussed the characteristic features of the Solar and Lunar geomagnetic tides in the low latitude region, after deter-mining the harmonic coefficients of S and L at Kodaikanal, Alibag, Honolulu, San Juan and Apia and making use of the harmonics for Huancayo and Ibadan deter-mined by earlier investigators. In order to understand the mechanism of these transient geomagnetic variations, it is worthwhile comparing the S and L variations, Earlier investigators (Onwumechilli and Alexander 1959) have taken the first com-ponent of S and the first component of L for comparison. As the principal component of the L variation is the second harmonic L2 and the principal component of the S variation is the first Si the comparison of L and S may be confined to Ls (H) and (H) in order to get a better physical picture of the phenomenon.